Altered expression and mutations in cell cycle genes CCND1, CDK4, CDKN2B and TP53 are associated with Pakistani breast cancer patients - Wajeeha Tariq; Ali Raza Awan; Asim Khalid Mahmood; Muhammad Wasim (Molecular Biology Reports, 2026)

Immunoinformatics-guided design of a multi-epitope vaccine targeting the envelopment polyprotein of oropouche virus - Muhammad Naveed; Aroosa Athar; Afifa Tariq; Muhammad Asim; Muhammad Nouman Majeed; Rania Ali El Hadi Mohamed; Manal F. Elkhadragy; Maher S. Alwethaynani; Mai M. Almsaud; Ghulam Nabi (Molecular Genetics and Genomics, 2026)

Phytochemical Analysis, Antioxidant and Pharmacological Evaluation of Antidiabetic Activity of Methanolic Extract of Geranium wallichianum D. Don ex Sweet in Alloxan-Induced Diabetic Rats - Fatima Afzal; Abdul Aleem; Javed Iqbal; Fahad Asim; Irfan Anjum; Muhammad Naveed Mushtaq (Journal of Pharmaceutical Innovation, 2026)

From commensal to pathobiont: The emergence of virulence-enhanced Escherichia coli in China's food-animal systems – insights with future implications - Nishant Shah; Asim Munir; Muhammad Shafiq; Muhammad Shoaib (Food Research International, 2026)

Dual upcycling of waste PET into both the porous support and the Al-MOF filler of thin film nanocomposite nanofiltration membranes - Aroosa Nehal; Aamir Razaq; Asim Laeeq Khan; Muhammad Yasin; Gianluca Viscusi; Giuliana Gorrasi; Mazhar Amjad Gilani; Beenish Shazadi (Journal of Water Process Engineering, 2026)

Corrigendum to “Green-synthesized silver nanoparticles from Moringa oleifera for eco-friendly management of citrus blast caused by Pseudomonas syringae” [South African Journal of Botany 196 (2026) 715–723] - Servish Munir; Javed Iqbal Wattoo; Muhammad Asim; Hotaf Hassan Makki (South African Journal of Botany, 2026)

Green-synthesized silver nanoparticles from Moringa oleifera for eco-friendly management of citrus blast caused by Pseudomonas syringae - Servish Munir; Javed Iqbal Wattoo; Muhammad Asim; Hotaf Hassan Makki (South African Journal of Botany, 2026)

Oxidation turns biodegradable microplastics into stronger stressors for soil nematodes and increases plant parasite risk with sawdust amendment - Zhongjie Sun; Yaxuan Cui; Yaru Nie; Yan He; Xiongde Dong; Muhammad Aaqil Khan; Feirong Ren; Hao liu; Shujaul Mulk Khan; Noshin Ilyas; Asim Shahzad; Junqiang Zheng (Applied Soil Ecology, 2026)

Dairy farm waste as a source of novel and globally disseminated multidrug-resistant Escherichia coli clones: A genomic and phylogeographic study - Muhammad Shoaib; Minjia Tang; Asim Munir; Muhammad Shafiq; Mashkoor Mohsin; Xuejing Zhang; Zhongyong Wu; Zhuolin He; Baocheng Hao; Shengyi Wang; Ruichao Li; Wanxia Pu (Journal of Hazardous Materials, 2026)

Erratum to: CRISPR, Omics, and Nanotechnology: A Triangular Strategy for Next-Generation Wheat Improvement - Muhammad Mubashar Zafar; Ayaz Haider Khan; Ali Murtaza; Muhammad Asim Jamil; Hafsa; Muhammad Munem Khan; Muhammad Awais; Hina Firdous (Journal of Crop Health, 2026)

Design of a multi-epitope vaccine candidate against Mycobacterium ulcerans for the prevention of Buruli ulcer - Muhammad Asim; Ramy S. Yehia; Hotaf Hassan Makki; Ahmed M. Ismail (Biologia, 2026)

Biocontrol of powdery mildew in luffa by the silicon-solubilizing endophytic fungi from Trichoderma koningii and Aspergillus clavatus - Asim Ur-Rahman; Sundus Rauf; Khalil Ur Rahman; Mamoona Rauf; Humaira Gul; Alaa Baazeem; Mohamed M. Hassan; Muhammad Hamayun; Muhammad Arif (Physiological and Molecular Plant Pathology, 2026)

The AI revolution in sustainable food processing: From process optimization to a circular bioeconomy - Asad A. Zaidi; Aisha Jilani; Muhammad Asif; Asim Laeeq Khan; Sohaib Z. Khan (Food and Bioproducts Processing, 2026)

Correction: Molecular characterization and green synthesis of iron oxide nanoparticles from Ureibacillus chungkukjangi for methylene blue degradation - Muhammad Naveed; Muhammad Asim; Tariq Aziz; Shumaila Ibrahim; Maida Salah Ud Din; Maryam M. Alomran; Ashwag Shami; Fakhria A. Al-Joufi; Ahmad A. Alghamdi; Abdullah A. Alqasem; Ahmed M. Basri; Majid Alhomrani (Antonie van Leeuwenhoek, 2026)

Antibacterial flavonoid derivatives: in silico ADMET, DFT, Molecular Docking, MD Simulation and in vitro verification - Atif Ishfaq; Affifa Tajammal; Riaz Maira; Aisha Waheed Qureshi; Babar Aleeza; Muhammad Asim Raza Basra (In Silico Pharmacology, 2026)

Electrospun nanofiber membranes for air filtration: Charge engineering, wettability control, antimicrobial function, and gas-phase removal - Nasrul Arahman; Afrillia Fahrina; Sri Mulyati; Lisendra Marbelia; Manhuwal Walad; Nova Kurnia; Muhammad Asy’ari; Asim Laeeq Khan; Muhammad Roil Bilad (Journal of Environmental Chemical Engineering, 2026)

Sewage Sludge-Mediated Microplastic Transfer to Agroecosystem: A Comprehensive Review on Detection, Fate and Ecological Impacts - Muhammad Tariq Khan; Masroor Waliullah; Zohaib Abbas; Saba Hafeez; Mohammad Bhuyan; Nasrin Akhter; Iqbal Ahmad; Asim Nawab; Mushtaq Ahmad; Yanbo Zhou; Md Faysal Hossain (Water, Air, & Soil Pollution, 2026)
Microplastic (MP) pollution has become a significant environmental concern due to its persistent nature and toxic environmental effects. MPs pose threats to the aquatic and terrestrial environment by impacting plant habitats and altering soil properties. Wastewater treatment plants (WWTPs) are one of the most prominent channels for MP pollution in both aquatic and terrestrial ecosystems. MP particles separated during various treatment processes are trapped in the sludge and subsequently enter the terrestrial agroecosystem when sludge is used as fertilizer. In addition, sludge incineration releases tiny MP particles into the atmosphere. Although MPs have been extensively studied in aquatic environments, limited studies are available regarding their transport to agricultural ecosystems and the pathways through which they pose risk to food security and soil fertility. This review aims to evaluate the prevalence of MPs within sewage sludge and their subsequent translocation into terrestrial agroecosystems. A critical investigation has been carried out to address the challenges in detecting MPs in complex sludge samples to provide guidance for developing standardized and widely accepted methodologies. Furthermore, the impacts of MPs on soil fertility and biota were assessed and investigated from the perspective of agricultural production. This review aims to compile evidence of the presence and transport of MPs through sewage sludge applied to agricultural lands and help policymakers and environmentalists in developing viable strategies to protect agricultural land from MP pollution. Graphical Abstract

CRISPR, Omics, and Nanotechnology: A Triangular Strategy for Next-Generation Wheat Improvement - Muhammad Mubashar Zafar; Ayaz Haider Khan; Ali Murtaza; Muhammad Asim Jamil; Hafsa; Muhammad Munem Khan; Muhammad Awais; Hina Firdous (Journal of Crop Health, 2026)

Synergistic biocontrol of Parthenium hysterophorus: the role of Curvularia specifera and Zygogramma bicolorata - Syed Muhammad Ziaullah; Muhammad Hamayun; Amjad Iqbal; Syed Asim; Sajid Ali; Anwar Hussain (Archives of Microbiology, 2026)

Integrative 16S rRNA characterization, pan-genome, and immunoinformatics approaches for the design of a multi-epitope vaccine against Bacillus cereus, a foodborne pathogen - Muhammad Asim; Muhammad Naveed; Tariq Aziz; Muhammad Toheed; Hafiz Muzzammel Rehman; Nawal Al-Hoshani; Rania Ali El Hadi Mohamed; Maher S. Alwethaynani; Areej A Alhhazmi; Manal F. Elkhadragy (World Journal of Microbiology and Biotechnology, 2026)

Bioprocess parameter screening and condition selection for single-cell protein production using yeast co-culture and agro-food waste substrates - Zukhruf Asim; Hafiz Muhammad Aamir Shahzad; Khalid Ouararhni; Fares Almomani; Kashif Rasool (Process Safety and Environmental Protection, 2026)

Molecular characterization and immunoinformatics-based design of a multi-epitope vaccine against Staphylococcus nepalensis - Muhammad Asim; Hotaf Hassan Makki (Antonie van Leeuwenhoek, 2026)

Paleodietary inferences of the Pleistocene (Pinjor Formation) ungulates from district Gujrat using mesowear analysis - Abrar Hussain; Muhammad Akbar Khan; Muhammad Asim; Sayyed Ghyour Abbas; Muhammad Adeeb Babar; Khalid Mahmood (Quaternary International, 2026)

Advances in membrane bioreactor and IFAS-MBR systems for treatment of wastewater containing pharmaceuticals - Ratri Rachmawati; Ibrahim Maina Idriss; Zubair Hashmi; Nova Kurnia; Indah Prihatiningtyas; Asim Laeeq Khan; Muhammad Roil Bilad (Journal of Environmental Chemical Engineering, 2026)

Natural antimicrobials as sustainable preservatives against postharvest microbial spoilage in fruits and vegetables - Aqleem Abbas; Yanyin Guo; Nana Ji; Shanshan Hao; Huihui Xu; Muhammad Asim (Food Bioscience, 2026)

Synergistic yeast co-culture and pretreatment optimization for enhanced single cell protein production from agro-waste - Zukhruf Asim; Hafiz Muhammad Aamir Shahzad; Khaled A. Mahmoud; Fares Almomani; Kashif Rasool (Biomass and Bioenergy, 2026)

Biosynthesis and Biological Assessment of TiO₂ Nanoparticles from Pittosporum Tobira for Antioxidant, Anti-Inflammatory, Anti-Hemolytic Potential, and Polychlorinated Biphenyls Degradation - Muhammad Naveed; Muhammad Asim; Tariq Aziz; Saman Nasir; Maida Salah Ud Din; Nawal Al-Hoshani; Maher S. Alwethaynani; Maymounah A. Alrayyani; Fakhria A. Al-Joufi (Water, Air, & Soil Pollution, 2026)

Isolation and molecular characterization of plant growth-promoting rhizobacteria for biocontrol of Fusarium head blight in wheat - Syed Jehangir Shah; Somaira Bibi; Safira Attacha; Syed Tanveer Shah; Noreen Asim; Waqas Ahmad; Muhammad Sayyar Khan; Ishrat Naz; Muhammad Ibrahim; Aftab Jamal (Cereal Research Communications, 2026)

Integrated energy and thermal analysis for residential buildings in karachi: A comprehensive audit approach - Shahzaib Hassan; Saqlain Abbas; Zahid Hussain; Ahmad Asim; Zulkarnain Abbas; Muhammad Aqib (Next Research, 2026)

Interface synergistic-driven electronic modulation in amorphous CoFeB@g-C3N4 for high-performance bifunctional OER/HER electrocatalysis - Abdul Haq; Anuj Kumar; Muhammad Arif; Umair Azhar; Huma Ahmad; Unaiza Talib; Mahnoor Ahmed; Muhammad Asim Mushtaq; Muhammad Sagir; Muhammad Faheem Maqsood; Kumar Venkatesan; Ghulam Yasin (Journal of Environmental Chemical Engineering, 2026)

Apocynin Loaded pH-Sensitive Nanoparticles Based Transdermal Hydrogel: an Innovative Therapeutic Approach against Rheumatoid Arthritis - Raskha Akbar; Dildar Khan; Muhammad Bilal Sabir; Irfa Basharat Rajput; Mona Al Hamod; Asim. ur. Rehman; Naz Dilawar; Shefaat Ullah Shah; Sakina Niyazi; Abdullah R. Alanzi; Hattan A. Alharbi; Kifayat Ullah Shah (Journal of Pharmaceutical Innovation, 2026)

Solar-Driven Photocatalytic Degradation of Organic Pollutants by I-MnO₂/PTh Nanocomposite: Mechanisms, Kinetics, and Implications for Advanced Environmental Remediation - Muhammad Nayab; Ahmad Farhan; Muhammad Zahid; Zulfiqar Ahmad Rehan; Asim Jilani; Rafa Almeer; Hussameldin Ibrahim; Nabil Al-Zaqri (International Journal of Environmental Research, 2026)

Genetic Characterization of Schistosoma Species from Goats in Pakistan Using the 28S rDNA Region - Muhammad Asim Khan; Kiran Afshan; Sabika Firasat; Muhammad Farhat Ullah; M. Ijaz Khan; Dilsora Abduvalieva (Indian Journal of Microbiology, 2026)

Molecular identification of the blaOXA gene in Bacillus cereus and AI-driven optimization of natural phytochemicals for foodborne illness treatment - Muhammad Naveed; Muhammad Asim; Tariq Aziz; Maida Salah Ud Din; Muhammad Nouman Majeed; Ammena Y. Binsaleh; Nawal Al-Hoshani; Maher S. Alwethaynani; Abeer M. Alghamdi; Fakhria A. Al-Joufi (Antonie van Leeuwenhoek, 2026)

Photoperiod and temperature: Key abiotic drivers of horticultural crop physiology in a changing climate - Muhammad Atiq Ashraf; Shumaila Nawaz; Uzma Bilal; Maria Abubakar; Shumaila Anam; Muhammad Azam; Burhan Khalid; Abdullah; Muhammad Asim; Rabbya Rayan Shah; Muhammad Ateeq (Biologia, 2026)

Biostimulant effect of seaweed extracts on micropropagation of important ground macrophyte Micranthemum tweediei and data-driven insights using machine learning and response surface regression - Esra Özcan; Seyid Amjad Ali; Muhammad Asim; Hasan Hüseyin Atar (Aquaculture International, 2026)
Commercially viable in vitro cultivation of ornamental and aquatic plants depends heavily on the proper use of bio-stimulants that encourage healthy and uniform growth. This study explores the role of two seaweed extracts, Jania rubens and Cystoseira barbata , in promoting in vitro micropropagation of Micranthemum tweediei (Monte Carlo), a widely used aquatic plant. Culture medium was enriched with different concentrations (2.5–20.0%) of J. rubens and C. barbata extracts with 1–4 g L −1 Murashige and Skoog (MS) nutrient media. Considering all results, J. rubens extract was more effective than C. barbata in terms of micropropagation and chlorophyll content of M. tweediei . Addition of 5% J. rubens extract to 2 g L −1 MS medium (approx. half strength) resulted in a 47% increase in clump diameter (5.18 cm), a 173% increase in rooting rate (92.4%), and a 108% increase in shoot clump fresh weight (3.6 g), and 84%, 115%, and 87% increases in chlorophyll a , b , and total chlorophyll levels, respectively, compared to the control 2 g L −1 MS medium without extract. Micropropagation parameters resulting from 4 g L −1 MS (approx. full strength) supplemented with J. rubens extract were lower than those obtained from 2 g L −1 MS. Unlike J. rubens , C. barbata showed the highest micropropagation when 10% extract was added to 4 g L −1 MS nutrient medium, resulting in a clump diameter of 5.11 cm, 42.8% rooting, a fresh clump weight of 7.37 g, and a dry clump weight of 0.59 g. Propagated in vitro plants were easily acclimated to external conditions in aquariums. Results of response surface regression analysis (RSRA) confirmed the results, and MS concentration influenced the plant biomass and chlorophyll contents, whereas seaweed type and concentration regulated the clump diameter and rooting. Application of machine learning models validated and predicted the outcomes precisely. Multi-layer perceptron (MLP) model exhibited superior predictive accuracy for morphological traits, while more predictive accuracy of chlorophyll parameters was attributed to Random Forest (RF) model. This study has shown for the first time that aquatic plants can be micropropagated more successfully and at lower cost by adding seaweed extracts to in vitro nutrient media without the need for growth regulators.

Adaptive responses of Pseudomonas marginalis to modified atmosphere packaging conditions - Muhammad Asim; Huihui Xu; Yanyin Guo; Aqleem Abbas; Mingkun Jiang; Nana Ji; Faryal Shaukat; Hengjia Ni; Zhengli Wang (International Journal of Food Microbiology, 2026)

pH-responsive MIL-101(Fe)/NiFe-LDH composite membranes for high-flux removal of cationic and anionic dyes in wastewater treatment - Shehriyar; Arslan Khurram; Abdul Jabbar; Muhammad Asim Khan; Wenhao Liu; Sadaf Mutahir; Akhtar Munir; Sameerah I. Al-Saeedi (Desalination, 2026)

Integrating Standardized Climate Indicators Using Triple and Scaled Triple Collocation to Develop an Agricultural Productivity Stress Index - Muhammad Asim Khan; Jianyi Lin; Mohammed M. A. Almazah; Ijaz Hussain; Hanen Louati; Mhassen. E. E. Dalam (Water Resources Management, 2026)

Environmental resistomes and antimicrobial resistance: integrating the One Health framework - Kainat Raziq; Ramish Saleem; Saba Zafar; Tayyaba Sanaullah; Muhammad Muzammil Nazir; Umm E. Ummara; Asim Abbasi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Sustainable materials for electric vehicle batteries: A comprehensive review of progress, challenges, and opportunities - Noor Hafidzah Jabarullah; Muhammad Saifullah Abu Bakar; Teguh Kurniawan; Asep Bayu Dani Nandiyanto; Asim Laeeq Khan; Fatin Amanina Azis; Muhammad Roil Bilad (Next Research, 2025)

Orange peel derived biochar assisted rGO@MoS₂ composite for visible light driven ciprofloxacin degradation and hydrogen evolution - Asim Jilani; Mohsin Raza Dustgeer; Mohammad Omaish Ansari; Alishbah Zaka; Muhammad Adil Mansoor; Ammar A. Melaibari; Hussameldin Ibrahim (Journal of Water Process Engineering, 2025)

Solubility measurements of R143a, R23 and R116 with [HMIM][TF2N] and [BMIM][BF4] - Nimra Javed; Muhammad Salman; Yiran Wang; Peiji Wang; Asim Shakeel; Xiangyang Liu; Maogang He (International Journal of Refrigeration, 2025)

Evaluation of Polystyrene Biodegradation: Characterization of biodegradation kinetics of Rhizopus oryzae Strain NA1 at Mesophilic Temperature - Sadia Mehmood Satti; Naima Atiq; Asim Abbasi; Safia Ahmed; Muhammad Adnan Shereen; Aftab Ahmad; Abeer Hashem; Najla A. Alshaikh; Graciela Dolores Avila-Quezada; Elsayed Fathi Abd-Allah (Water, Air, & Soil Pollution, 2025)

Sedimentology and biostratigraphy of the Cretaceous–Paleocene successions in Northern Pakistan: evidence from the Hazara, Kala Chitta, Potwar, and Kohat Basins - Syed Kamran Ali; Hafiz Sohaib Bashir; Asim Qadir; Muhammad Saleem Mughal; Khurram Iqbal; Abrar Niaz; Khawaja Umair Majeed (Carbonates and Evaporites, 2025)

A Brief Outlook on the Preparation and Magnetic Properties of Iron Oxide Nanoparticles for Water Remediation - Younas Iqbal; Wencong Ma; Xuhui Li; Shenglei Fu; Asim Shahzad; Imtiaz Ahmad; Yangyang Wang; Muhammad Adil; Mohammad Abohashrh (Water, Air, & Soil Pollution, 2025)

Artificial neural network optimized green synthesis of cysteine-conjugated silver nanoparticles for antibacterial activity against staphylococcus nepalensis to combat cystitis - Muhammad Asim; Muhammad Naveed; Tariq Aziz; Maida Salah Ud Din; Fatma Alshehri; Ashwag Shami; Maher S. Alwethaynani; Deema Fallatah; Abeer M. Alghamdi; Fakhria A. Al-Joufi (Antonie van Leeuwenhoek, 2025)

Microwave synthesis of rock-salt type high entropy oxides immobilized on graphene oxide nanosheets as an efficient catalyst for oxygen evolution reaction - Muhammad Asim; Akbar Hussain; Meryem Samancı; Ayşe Bayrakçeken; Andrea Straková Fedorková; Naveed Kausar Janjua (Journal of Environmental Chemical Engineering, 2025)

Integrated transcriptomic and metabolomic analysis reveals dynamic changes in endogenous hormones and their potential associations with wound healing in broccoli stalk incisions during the self-adaptive stage (SAS) - Hengjia Ni; Hua He; Yanyin Guo; Qingyue Xue; Mingkun Jiang; Asim Muhammad; Nana Ji (Food Bioscience, 2025)

CdS nanoparticles boost charge transfer kinetics of NiCo layered bimetallic hydroxides to obtain high-capacity supercapacitors - Jiawei Jiang; Yu Xie; Long Zhang; Xiang Wang; Yuxuan Chen; Yaru Cheng; Muhammad Asim Mushtaq; Yue Guo; Jie Zhao (Chemical Engineering Journal, 2025)

Ring opening of epoxides: a facile approach towards the synthesis of polyketides and related stereoenriched natural products: a review - Madiha Hanif; Asim Mansha; Kulsoom Ghulam Ali; Muhammad Athar Saeed; Shahid Mahmood; Aijaz Rasool Chaudhry; Ahmad Irfan; Aqsa Mushtaq; Ameer Fawad Zahoor (Molecular Diversity, 2025)

Molecular characterization and green synthesis of iron oxide nanoparticles from Ureibacillus chungkukjangi for methylene blue degradation - Muhammad Naveed; Muhammad Asim; Tariq Aziz; Shumaila Ibrahim; Maida Salah Ud Din; Maryam M. Alomran; Ashwag Shami; Fakhria A. Al-Joufi; Ahmad A. Alghamdi; Abdullah A. Alqasem; Ahmed M. Basri; Majid Alhomrani (Antonie van Leeuwenhoek, 2025)

Retraction notice to “Template-based textural modifications of polymeric graphitic carbon nitrides towards waste water treatment” [Chemosphere 302, September 2022,134792] - Umair Azhar; Muhammad Sohail Bashir; Muhammad Babar; Muhammad Arif; Afaq Hassan; Asim Riaz; Rana Mujahid; Muhammad Sagir; Saadat Ullah Khan Suri; Pau Loke Show; Jo-Shu Chang; Kuan Shiong Khoo; et al. (Chemosphere, 2025)

Synergizing ZIF-67 activity with polyetherimide to achieve dendrite and shuttle-free lithium sulfur batteries - Waseem Raza; Andleeb Mehmood; Arshad Hussain; Karma M. Albalawi; Munir Ahmad; Muhammad Ahmed; Manal S. Ebaid; Muhammad Asim Mushtaq; Nadeem Raza; Huayu Huang; Lihong Ao; Dongqing Liu; et al. (Chemical Engineering Journal, 2025)

Retraction Note: Anti-rheumatic activity of pseudoephedrine (a substituted phenethylamine) in complete Freund’s adjuvant-induced arthritic rats by down regulating IL-1β, IL-6 and TNF-α as well as upregulating IL-4 and IL-10 - Haseeb Ahsan; Hafiz Muhammad Irfan; Alamgeer; Muhammad Shahzad; Mulazim Hussain Asim; Muhammad Akram; Muhammad Shoaib Zafar (Inflammopharmacology, 2025)

Enhanced you only look once v5s crack detection and classification technique by optimizing transformer architecture and convolutional complexity - Umar Ali; Muhammad Arshad Shehzad Hassan; Asim Khan; Muhammad Zeeshan Khan; Maryam Shahzadi (Innovative Infrastructure Solutions, 2025)

Green chemistry for prostate health: exploring nature’s toolbox against cancer, inflammation, and hyperplasia - Muavia Sarwar; Hafiz Muhammad Irfan; Alamgeer; Zeeshan Jabbar; Mulazim Hussain Asim; Muhammad Sajjad Hassan; Shoaib Nawaz (Molecular Diversity, 2025)

New AI explained and validated deep learning approaches to accurately predict diabetes - Ifra Shaheen; Nadeem Javaid; Nabil Alrajeh; Yousra Asim; Syed Muhammad Abrar Akber (Medical & Biological Engineering & Computing, 2025)

Review on crack detection in civil infrastructure using structural health monitoring and machine learning techniques - Muhammad Zeeshan Khan; Maryam Shahzadi; Asim Khan; Umar Ali; Muhammad Arshad Shehzad Hassan; Majid Hussain (Innovative Infrastructure Solutions, 2025)

Anthropogenic dust pollution influences leaf and root morpho-anatomical traits by altering the metabolism and biochemical properties of indigenous vegetation - Muhammad Asim Sultan; Iftikhar Ahmad; Muhammad Arif; Saima Sadaf; Muhammad Kamran; Toqeer Abbas; Shifa Shaffique; Mansour K. Gatasheh (Environmental Geochemistry and Health, 2025)

Determination of heavy metals and morphoanatomical characteristics of the monocots Aristida mutabilis and Cenchrus ciliaris in the dust-contaminated stone crushing industry of Sargodha, Pakistan - Muhammad Asim Sultan; Iftikhar Ahmad; Muhammad Arif; Saud Alamri; Manzer H Siddiqui; Saima Sadaf; Muhammd Kamran (Environmental Monitoring and Assessment, 2025)

Petrogenesis and tectonic implications of Paleozoic S-type granitic gneisses of Nanga Parbat Syntaxis, North Pakistan - Amjad Hussain; Kui-Dong Zhao; Delores M. Robinson; Sakine Moradi; Muhammad Sajid; Hafiz U. Rehman; Qian Li; Syed Mumtaz Hussain; Rahat Ali; Syed Asim Hussain (Lithos, 2025)

A critical review on pear Fruit’s polyphenols and its chlorogenic acid: Composition, bioavailability, and pharmacological potential - Abdul Basit; Raheem Shahzad; Abdul Mueed; Asim Muhammad; Wang Rong; Liu Ya; Gong Xin; Khanizadeh Shahrokh; Muhammad Arshad; Tao Shutian (Food Bioscience, 2025)

Recent advances in synthesis and modulation of 2D heterostructures for sensing and detection applications - Rumaisa Tariq; Waseem Raza; Karma M. Albalawi; Arshad Hussain; Munir Ahmad; Muhammad Asim Mushtaq; Mohamed H. Helal; Ibrahim A. Shaaban; Shaukat Khan; Muhammad Sufyan Javed (Chemical Engineering Journal, 2025)

Unraveling the influence of doleritic intrusions on diagenetic alterations in the Precambrian Utch Khattak Limestone, Gandghar Range, Pakistan - Muhammad Asim; Mumtaz Muhammad Shah; Sajjad Khan (Carbonates and Evaporites, 2025)

Effect of Diagenetic Processes and Depositional Facies on Reservoir Quality of the Eocene Carbonate Sequence (Sakesar Limestone) in the Central Salt Range, Pakistan - Naveed Rehman; Shu Jiang; Syed Haroon Ali; Asim Falak Naz; Muhammad Tariq (Journal of Earth Science, 2025)

miR-107 suppresses porcine granulosa cell proliferation and estradiol synthesis while promoting apoptosis via targeting PTGS2 - Shuhan Liu; Jiahao Chen; Mingzheng Liu; Chunlei Zhang; Xiaohuan Chao; Huan Yang; Tianshuo Wang; Hongwei Bi; Yuan Ding; Ziming Wang; Asim Muhammad; Mubashir Muhammad; et al. (Theriogenology, 2025)

The role of nitric oxide and nitrogen in mediating copper stress in Brassica juncea L. - Bilal A. Rather; Asim Masood; Fei Qiao; Xuefei Jiang; Muhammad Mubashar Zafar; Hanqing Cong; Nafees A. Khan (Plant Science, 2025)

Paving the path to water security: The role of advanced adsorbents in wastewater treatment - Mushtaq Hussain; Asim Riaz; Hassan Zeb; Awais Ali; Rana Mujahid; Farooq Ahmad; Muhammad Shahzad Zafar (Journal of Water Process Engineering, 2025)

Exploring ultraviolet and nitrous acid-induced mutagenesis of Rhizopus oligosporus for extracellular inulinase production under solid-state culture - Syeda Wajiha Khalid; Sikander Ali; Sadaf Mutahir; Muhammad Asim Khan; Abdulrahman A. Almehizia; Jahangir Khan; Amna Waseem (Brazilian Journal of Microbiology, 2025)

In-silico structural and functional analysis of nonsynonymous single nucleotide polymorphisms in human FOLH1 gene - Abtin Tondar; Muhammad Irfan; Sergio Sánchez-Herrero; Hafsa Athar; Aleena Haqqi; Asim Kumar Bepari; Laura Calvet Liñán; David Hervás Marin (In Silico Pharmacology, 2025)

Paleocene Katisho ultramafic-mafic-intermediate igneous rocks in the Ladakh Batholith, northern Pakistan: Implications for the transition from intra-oceanic to Andean type arc setting - Zahid Hussain; Chuan-Lin Zhang; Masumeh Sargazi; Irfan Maqbool Bhat; Xian-Tao Ye; Zhi-Hao Song; Muhammad Farhan; Zaheen Ullah; Tehseen Zafar; Amjad Hussain; Syed Asim Hussain (Lithos, 2025)

Transcriptomics and metabolomics profiling revealed the adaptive mechanism of Penicillium digitatum under modified atmosphere packaging-simulated gas stress - Zhengli Wang; Shanshan Hao; Huihui Xu; Nana Ji; Yanyin Guo; Muhammad Asim (Postharvest Biology and Technology, 2025)

Microwave-assisted, sulfhydryl-modified β-cyclodextrin-silymarin inclusion complex: A diverse approach to improve oral drug bioavailability via enhanced mucoadhesion and permeation - Shumaila Arshad; Syed Atif Raza; Alamgeer; Syed Nasir Abbas Bukhari; Nasser F. Alotaibi; Naveed Ahmad; Hafiz Muhammad Irfan; Arshad Mahmood; Mulazim Hussain Asim (Carbohydrate Polymers, 2025)

Optimizing support vector machines for enhanced permeability prediction in sandstone reservoirs using systematic and heuristic hyperparameter tuning - Jar Ullah; Huan Li; Rifaat M. Abdalla; Muhammad Asad; Amos P. K. Tai; Asim Falaknaz (Earth Science Informatics, 2025)

A study on the performance of enhancing environmental protection from molecular iodine using granular impregnated activated carbon - Talhat Yaqoob; Masroor Ahmad; Attaullah Shah; Amjad Farooq; Farman Ali; Sahid Mehmood; Sidra Shaoor Kiani; Muhammad Asim Irshad; Azeem Bibi; Naseem Irfan (Environmental Science and Pollution Research, 2024)

A robust and simple non-enzymatic electrochemical sensor based on carbon dots-metal oxide composite for the detection of metronidazole traces in food products - Hafiza Khadija Aslam; Sehrish Bilal; Sana Mir; Sobia Tabassum; Mazhar Amjad Gilani; Mustansara Yaqub; Muhammad Asim (Food Chemistry, 2024)

Fabrication and characterization of bioactive curdlan and sodium alginate films for enhancing the shelf life of Volvariella volvacea - Asif Ali Khan; Feng-Jie Cui; Muhammad Wajid Ullah; Abdul Qayum; Ibrahim Khalifa; Syed Asim Shah Bacha; Zheng-Zi Ying; Ismail Khan; Umar Zeb; Abdullah A. Alarfaj; Mohammad Javed Ansari; Yan Yang; et al. (Food Bioscience, 2024)

Structure-property relationship of ultrasound-assisted nanoemulsion-impregnated bioactive polysaccharide films for enhanced shelf life of mushrooms - Asif Ali Khan; Muhammad Wajid Ullah; Abdul Qayum; Ibrahim Khalifa; Mazhar Ul-Islam; Syed Asim Shah Bacha; Umar Zeb; Fang-Jie Yao; Sulaiman Ali Alharbi; Mansour Shrahili; Yan Yang; Wei Jia; et al. (Food Packaging and Shelf Life, 2024)

Wood biochar induced metal tolerance in Maize (Zea mays L.) plants under heavy metal stress - Atiqa Zahra; Sadaf Kayani; Asim Shahzad; Tijen Demiral Sert; Hasan Ozcelik; Mingzhou Qin; Muhammad Naeem; Motsim Billah (Environmental Research, 2024)

Evaluating machine learning approaches for aboveground biomass prediction in fragmented high-elevated forests using multi-sensor satellite data - Asim Qadeer; Muhammad Shakir; Li Wang; Syed Muhammad Talha (Remote Sensing Applications: Society and Environment, 2024)

Preparation and functional characterization of pullulan-sodium alginate composite film enhanced with ultrasound-assisted clove essential oil Nanoemulsions for effective preservation of cherries and mushrooms - Arif Rashid; Abdul Qayum; Syed Asim Shah Bacha; Qiufang Liang; Yuxuan Liu; Lixin Kang; Zhuzhong Chi; Runhao Chi; Xu Han; John-Nelson Ekumah; Muhammad Safi Ullah Virk; Xiaofeng Ren; et al. (Food Chemistry, 2024)

Novel pullulan-sodium alginate film incorporated with anthocyanin-loaded casein-carboxy methyl cellulose nanocomplex for real-time fish and shrimp freshness monitoring - Arif Rashid; Abdul Qayum; Syed Asim Shah Bacha; Qiufang Liang; Yuxuan Liu; Lixin Kang; Zhuzhong Chi; Runhao Chi; Xu Han; John-Nelson Ekumah; Muhammad Safiullah Virk; Xiaofeng Ren; et al. (Food Hydrocolloids, 2024)

In vitro and in vivo modulatory effects of fluoxetine on gene expression and antioxidant enzymes in CFA-induced chronic inflammatory model: drug repurposing for arthritis - Hafiz Muhammad Irfan; Awais Anjum; Mulazim Hussain Asim; Saeed Ur Rasheed; Alamgeer; Farzana Siddique (Inflammopharmacology, 2024)

CRISPR/Cas-mediated genome editing for efficient tomato breeding: past achievements and future directions - Muhammad Naeem; Wajid Zaman; Saddam Saqib; Asim Shahzad; Saeed ur Rahman; Naveed Ahmad (South African Journal of Botany, 2024)

Optimizing cultural conditions and pretreatment for high-value single-cell protein from vegetable waste - Hafiz Muhammad Aamir Shahzad; Zukhruf Asim; Khaled A. Mahmoud; Omer M.A. Abdelhadi; Fares Almomani; Kashif Rasool (Process Safety and Environmental Protection, 2024)

Mapping the global spatial dynamics: renewable energy’s impact on air pollution spillovers in high-contaminant regions - Syed Jaffar Abbas; Asim Iqbal; Muhammad Munawar Hussain; Aftab Anwar (Environment, Development and Sustainability, 2024)

Unraveling the role of natural functional oils in modulating osteoarthritis related complications - Muhammad Asim Shabbir; Fakiha Mehak; Moazzam Rafiq Khan; Waqar Ahmed; Muhammad Furqan Nawaz; Abdo Hassoun; Zuhaib F. Bhat; Rana Muhammad Aadil (Critical Reviews in Food Science and Nutrition, 2024)

Re-examination of effects of pairing gaps on charge-changing transitions - Jameel-Un Nabi; Muhammad Tahir; Asim Ullah; Zeeshan Khan; Muhammad Aswad Ali Shah (Advances in Space Research, 2024)

A Comprehensive on Synthesis and Antimicrobial Evaluation of Substituted-Arylideneamino-5-(5-Chlorobenzofuran-2-yl)-1, 2, 4-Triazole-3-Thiol Derivatives/ Schiff Bases - Muhammad Rizwan; Sobia Noreen; Sadia Asim; Zohaib Liaqat; Hina Ibrahim; Rimsha Talib (Journal of Fluorescence, 2024)

Early detection of deep-seated smouldering fires in wood waste storage using ERT - Muhammad Asim Ibrahim; Nabeel Afzal Butt; Simon Rejkjær; Torleif Dahlin; Dan Madsen; Konard Wilkens Flecknoe-Brown; Thomas Günther (Waste Management, 2024)

Bio-upcycling of plastic waste: a sustainable innovative approach for circular economy - Sadia Mehmood Satti; Muzna Hashmi; Mishal Subhan; Muhammad Adnan Shereen; Adham Fayad; Asim Abbasi; Aamer Ali Shah; Hayssam M. Ali (Water, Air, & Soil Pollution, 2024)

ANN and regression based quantification framework for climate change impact assessment on a weak transmission grid of a developing country across Horizon 2050 plus - M. Mahad Malik; Hamza Waheed Asim; Syed Ali Abbas Kazmi; Kamran Mujahid; Muhammad Waleed Ansari (Environment, Development and Sustainability, 2024)

Efficacy of different blood meals for the mass rearing of Aedes aegypti (Diptera: Culicidae) population - Shahid Majeed; Muhammad Sufyan; Asim Abbasi; Muhammad Binyameen; Ramish Saleem; Wafa A. H. Alkherb; Shahla Faisal; Jamil Ijaz; Hira Hameed (International Journal of Tropical Insect Science, 2024)

Optimized design and analysis of cable-based parallel manipulators for enhanced subsea operations - Asim Ghaffar; Muhammad Zia Ur Rahman; Víctor Leiva; Cecilia Castro (Ocean Engineering, 2024)

Middle Miocene “Giraffa” from the Chinji Formation of Siwaliks, Pakistan - Muhammad Asim; Kiran Aftab; Muhammad Akbar Khan; Sayyed Ghyour Abbas; Muhammad Adeeb Babar; Mubashar Hussain; Sania Saeed (Palaeoworld, 2024)

Structural and thermal investigation of lignocellulosic biomass conversion for enhancing sustainable imperative in progressive organic refinery paradigm for waste-to-energy applications - Tayyab Qureshi; Muhammad Farooq; Shahid Imran; Muhammad Adeel Munir; Muhammad Asad Javed; Ihsanullah Sohoo; Muhammad Sultan; Ateekh Ur Rehman; Muhammad Farhan; Muhammad Asim; John M. Andresen (Environmental Research, 2024)

Strategies for Crossing Biological Barriers in Drug Delivery - Muhammad Awais; Salma Batool; Mahnoor Khan; Laiba Asim; Rabia Riaz; Rimsha Zafar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2024)

Reduced graphene oxide supported polyaniline/copper (II) oxide nanostructures for enhanced photocatalytic degradation of Congo red and hydrogen production from water - Mohsin Raza Dustgeer; Asim Jilani; Mohammad Omaish Ansari; Muhammad Bilal Shakoor; Shafaqat Ali; Aniqa Imtiaz; Hazirah Syahirah Zakria; Mohd Hafiz Dzarfan Othman (Journal of Water Process Engineering, 2024)

Covalent organic polymers for efficient removal of iodine from gas- and liquid-phase environments - Haishan Zhu; Yuancheng Qin; Yue Guo; Zhen Shen; Muhammad Imran; Muhammad Asim Mushtaq; Zhiqi Zhang; Cailing Ni; Yanqing Chen; Yangbin Ding; Hajera Gul; Jianping Zou; et al. (Chemical Engineering Journal, 2024)

Impact of Various Combinations of Organic and Inorganic Fertilizers on Fruit Production and Quality of ‘Kinnow’ Mandarin (Citrus reticulata Blanco.) - Muhammad Asim; Faisal Hayat; Tehseen Ashraf; Fakhara Khanum; Juan Li; Yang Peng; Yanxiao Ma; Shahid Iqbal; Ummara Khan; Sitwat Riaz; Panfeng Tu; Fiaz Hussain; et al. (Applied Fruit Science, 2024)

Efficient electrocatalytic reduction of nitrate to ammonia over Mo2CTx micro-foam with rich edge sites - Yanyan Wu; Kanghui Yao; Ziwei Zhao; Zhansheng Lu; Qianqian Ji; Jie Zhao; Yongjie Wang; Jiaqi Zhu; Muhammad Asim Mushtaq; Huarui Sun; Panagiotis Tsiakaras; Xingke Cai (Chemical Engineering Journal, 2024)

Quantifying future water-saving potential under climate change and groundwater recharge scenarios in Lower Chenab Canal, Indus River Basin - Muhammad Shafeeque; Mohsin Hafeez; Abid Sarwar; Arfan Arshad; Tahira Khurshid; Muhammad Irfan Asim; Shoaib Ali; Adil Dilawar (Theoretical and Applied Climatology, 2024)
Quantifying water-saving potential (WSP) is crucial for sustainable water resource management in canal command areas and river basins. Previous studies have partially or fully ignored the importance of groundwater in WSP assessments, particularly in irrigated areas. This study is aimed at quantifying WSP in the Lower Chenab Canal (LCC) command area of the Indus River Basin, Pakistan, under various scenarios of future climate change and groundwater recharge. These quantifications are conducted using an empirical model based on the Budyko theory. The model was forced using observed, remote sensing, and CMIP6 future climate data for two Shared Socioeconomic Pathways (SSP245 and SSP585) and their ensembles (cold-dry, cold-wet, warm-dry, and warm-wet) for possible futures. The results showed that the average WSP in the LCC command area was 466 ± 48 mm/year during the historical period (2001–2020). The WSP is projected to decrease by – 68 ± 3% under the warm-dry ensemble scenario (SSP245 and SSP585) and – 48 ± 13% under the ensembled cold-wet scenario by 2100. The results also demonstrated that WSP could be increased by up to 70 ± 9% by artificially recharging 20% of the abstracted groundwater per year in the LCC command area by the late twenty-first century. Our findings highlight the importance of adopting artificial groundwater recharge to enhance the WSP and sustainably manage water resources in the LCC command area. Policymakers should consider these findings when deciding on water resource management in the Indus River Basin.

Experimental and numerical study of an innovative twined tube HX design - Muhammad Ali Khan; Muhammad Daniyal Khalid; Muhammad Ilyas; Muhammad Daniyal Nauman; Muhammad Asim; Khalid Waheed; Fatih Aydogan (Annals of Nuclear Energy, 2024)

Pathological effects of feeding aflatoxin-contaminated feed on immune status and reproductive performance of juvenile white leghorn males and its mitigation with ∝-tocopherol and Moringa oleifera - Muhammad Kashif Saleemi; Ahmad Raza; Aisha Khatoon; Muhammad Zubair; Shafia Tehseen Gul; Xu Yongping; Bilal Murtaza; Faqir Muhammad; Bushra Akhtar; Farhat Jubeen; Farzana Rizvi; Khawar Zubair; et al. (Environmental Science and Pollution Research, 2023)

Corrigendum to “Automated anomalous behaviour detection in soil radon gas prior to earthquakes using computational intelligence techniques” [J. Environ. Radioact. 203 (2019) 48-54] - Aleem Dad Khan Tareen; Asim Khawaja; Kimberlee Jane Kearfott; Muhammad Rafique; Malik Sajjad Ahmed Nadeem; Talat Iqbal; Saeed Ur Rahman (Journal of Environmental Radioactivity, 2023)

Retention of methyl iodide on metal and TEDA impregnated activated carbon using indigenously developed setup - Talhat Yaqoob; Masroor Ahmad; Yasir Faiz; Farman Ali; Amjad Farooq; Faisal Faiz; Attaullah Shah; Muhammad Asim Irshad; Naseem Irfan; Nisar Ali; Sahid Mehmood (Environmental Research, 2023)

Evaluating the influence of green growth, institutional quality and financial inclusion on financial stability: evidence by sustainable finance theory - Muhammad Sajid; Muhammad Akbar Ali Ansari; Arsalan Tanveer; Muhammad Faheem; Asim Waseem (Environmental Science and Pollution Research, 2023)

Investigating catalytic oxidative desulfurization of model fuel using hollow PW12/TiO2@MgCO3 and performance optimization via box-behnken design - Sadaf Ul Hassan; Hamna Khalid; Sidra Shafique; Muhammad Asim Farid; Muhammad Haris Saeed; Zulfiqar Ali; Muhammad Shahid Nazir; Murid Hussain; Young-Kwon Park (Chemosphere, 2023)

Paper based colorimetric sensor using novel green magnetized nanocomposite of pinus for hydrogen peroxide detection in water and milk - Mehrosh Buzdar; Asim Yaqub; Akhtar Hayat; Muhammad Zia Ul Haq; Aizaz Khan; Huma Ajab (Food Bioscience, 2023)

Edge-hosted CoFeB active sites with graphene nanosheets for highly selective nitrogen reduction reaction towards ambient ammonia synthesis - Muhammad Arif; Anuj Kumar; Muhammad Asim Mushtaq; Umair Azhar; Muhammad Sagir; Muhammad Bilal Tahir; Unaiza Talib; Saira Ajmal; Khalid M. Alotaibi; Ghulam Yasin (Chemical Engineering Journal, 2023)

Life table parameters and feeding potential of Chrysoperla carnea (Stephens) on eggs of Pyrilla perpusilla (Walker) - Muhammad Umer; Javed khan; Fan Fan; Xiaofan Yang; Mengyao Li; Asim Iqbal; Guoshu Wei (Journal of Plant Diseases and Protection, 2023)

Mucoadhesive, Fluconazole-Loaded Nanogels Complexed with Sulfhydryl-β-cyclodextrin for Oral Thrush Treatment - Farwa Muskan Khalid; Muhammad Ijaz; Arshad Mahmood; Muhammad Khurram Waqas; Talib Hussain; Mulazim Hussain Asim; Nadeem Ahmad; Shumaila Arshad; Masood Ur Rehman; Imran Nazir (AAPS PharmSciTech, 2023)

Correction to: Molecular and genetic insights into secondary metabolic regulation underlying insect‑pest resistance in legumes - Muhammad Khuram Razzaq; Aiman Hina; Asim Abbasi; Benjamin Karikari; Hafiza Javaria Ashraf; Muhammad Mohiuddin; Sumaira Maqsood; Aqsa Maqsood; Inzamam Ul Haq; Guangnan Xing; Ghulam Raza; Javaid Akhter Bhat (Functional & Integrative Genomics, 2023)

Molecular and genetic insights into secondary metabolic regulation underlying insect-pest resistance in legumes - Muhammad Khuram Razzaq; Aiman Hina; Asim Abbasi; Benjamin Karikari; Hafiza Javaria Ashraf; Muhammad Mohiuddin; Sumaira Maqsood; Aqsa Maqsood; Inzamam Ul Haq; Guangnan Xing; Ghulam Raza; Javaid Akhter Bhat (Functional & Integrative Genomics, 2023)

Exploring the Intertwined Nexus between Globalization, Energy Usage, Economic Complexity, and Environmental Quality in Emerging Asian Economies: A Pathway Towards a Greener Future - Muhmmad Asim Rafiq; Abdul Rauf; Saifullah Shakir; Ameer Muhammad Aamir Abbas; Huaping Sun; Saira Abid (Environmental Science and Pollution Research, 2023)

Exploring the relationships between attitudes toward emission trading schemes, artificial intelligence, climate entrepreneurship, and sustainable performance - Bin Hu; Shoaib Asim; Muhammad Sibt-e-Ali; Muhammad Qasim Javaid; Muhammad Ramzan (Environmental Science and Pollution Research, 2023)

Histopathology and antibody responses describe the seasonal pattern of dicrocoeliosis in small ruminants in the Himalayan ranges of Pakistan - Muhammad Asim Khan; Kiran Afshan; Umer Chaudhry; Sabika Firasat; Neil D. Sargison (Veterinary Parasitology, 2023)

Usage of the XGBoost and MARS algorithms for predicting body weight in Kajli sheep breed - Asim Faraz; Cem Tırınk; Hasan Önder; Uğur Şen; Hafiz Muhammad Ishaq; Nasir Ali Tauqir; Abdul Waheed; Muhammad Shahid Nabeel (Tropical Animal Health and Production, 2023)

Impact of green HRM practices on sustainable performance: mediating role of green innovation, green culture, and green employees’ behavior - Muhammad Asim Shahzad; Du Jianguo; Muhammad Junaid (Environmental Science and Pollution Research, 2023)

Synergistic photocatalytic performance of Fe@Fe2O3 core-shell nanostructures supported on g-C3N4 nanosheets for RhB and phenol decolorization: Fabrication, characterization, and mechanistic insights - Shahid Iqbal; Jianjun Liu; Hecheng Ma; Wenqi Liu; Shengli Zuo; Yingchun Yu; Ni Yan; Muhammad Asim Mushtaq (Journal of Water Process Engineering, 2023)

Impact of alternate Mn doping in ternary nanocomposites on their structural, optical and antimicrobial properties: Comparative analysis of photocatalytic degradation and antibacterial activity - Noor Tahir; Muhammad Zahid; Asim Jillani; Suman Tahir; Muhammad Yaseen; Qamar Abbas; Rana Abdul Shakoor; Syed Zajif Hussain; Imran Shahid (Journal of Environmental Management, 2023)

Machine learning - a novel approach to predict the porosity curve using geophysical logs data: An example from the Lower Goru sand reservoir in the Southern Indus Basin, Pakistan - Wakeel Hussain; Miao Luo; Muhammad Ali; Syed Mumtaz Hussain; Sajid Ali; Sartaj Hussain; Asim Falak Naz; Saddam Hussain (Journal of Applied Geophysics, 2023)

A critical review in recent progress of hollow fiber membrane contactors for efficient CO2 separations - Aniqa Imtiaz; Mohd Hafiz Dzarfan Othman; Asim Jilani; Imran Ullah Khan; Roziana Kamaludin; Muhammad Ayub; Ojo Samuel; Tonni Agustiono Kurniawan; NurAwanis Hashim; Mohd Hafiz Puteh (Chemosphere, 2023)

Adsorption of hexavalent chromium ions in industrial effluent on low cost magnetized wood saw dust decayed by Isoptera (Termite): An insight into kinetics, equilibrium and thermodynamics studies - Mehpara Khatoon; Huma Ajab; Asim Yaqub; Muhammad Zia Ul Haq; Muhammad Junaid (Journal of Environmental Chemical Engineering, 2023)

The changing landscape of agriculture: role of precision breeding in developing smart crops - Amna Chaudhry; Ahtsham Ul Hassan; Sultan Habibullah Khan; Asim Abbasi; Aiman Hina; Muhammad Tajammal Khan; Nader R. Abdelsalam (Functional & Integrative Genomics, 2023)

Mineralogy and PGE geochemistry of chromitites and peridotites of the sapat complex in the indus suture zone, northern Pakistan: implications for magmatic processes in the supra-subduction zone - Zaheen Ullah; Huan Li; Asad Khan; Shah Faisal; Yildirim Dilek; Michael W. Förster; Muhammad Farhan; Umar Ashraf; Salman Ahmed Khattak; Gohar Rehman; Syed Asim Hussain (International Geology Review, 2023)

The environmental cost of FDI and spatial implications of CO2 emissions in Sub-Saharan Africa - Syed Jaffar Abbas; Asim Iqbal; Muhammad Munawar Hussain; Aftab Anwar (Environmental Science and Pollution Research, 2023)

Farm households' perception and adaptation to climate change in relation of food crop productivity in Pakistan - Seher Muneer; Khuda Bakhsh; Rafaqet Ali; Muhammad Asim Yasin; Muhammad Asif Kamran (Environment, Development and Sustainability, 2023)

Macroalgal biochar synthesis and its implication on membrane fouling mitigation in fluidized bed membrane bioreactor for wastewater treatment - Muhammad Maaz; Muhammad Aslam; Muhammad Yasin; Asim Laeeq Khan; Azeem Mushtaq; Tahir Fazal; Ahmed Muteb Aljuwayid; Mohamed A. Habila; Jeonghwan Kim (Chemosphere, 2023)

Dose optimization of silicon for boosting arbuscular mycorrhizal fungi colonization and cadmium stress mitigation in maize (Zea mays L.) - Ubaid Ullah Zia; Abdul Rehman Niazi; Zahoor Ahmad; Hesham F. Alharby; Ejaz Ahmad Waraich; Asim Abbasi; Muhammad Aamir Iqbal; Sarfraz Ahmed; Shozab Hina (Environmental Science and Pollution Research, 2023)

Performance evaluation of phosphonium based deep eutectic solvents coated cerium oxide nanoparticles for CO2 capture - Tausif Ahmad; Jibran Iqbal; Mohamad Azmi Bustam; Muhammad Babar; Muhammad Bilal Tahir; Muhammad Sagir; Muhammad Irfan; Hafiz Muhammad Anwaar Asghar; Afaq Hassan; Asim Riaz; Lai Fatt Chuah; Awais Bokhari; et al. (Environmental Research, 2023)

Molecular evidence of Ehrlichia canis, associated risk factors and hematobiochemical analysis in client owned and shelter cats of Pakistan - Syed Nazar Abbas; Muhammad Ijaz; Rao Zahid Abbas; Muhammad Hassan Saleem; Asim Khalid Mahmood (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Benzotriazole-based structure in porous organic polymer enhancing O2 activation for high-efficient degradation of tetracycline under visible light - Yuancheng Qin; Zhenhua Jiang; Yue Guo; Muhammad Asim Mushtaq; Zhen Shen; Wanjun Du; Cailing Ni; Geng Luo; Yu Ji; Zhiqi Zhang; Yonggui Deng; Arshad Hussain; et al. (Chemical Engineering Journal, 2023)

Spatial Distribution of Dicrocoelium in the Himalayan Ranges: Potential Impacts of Ecological Niches and Climatic Variables - Muhammad Asim Khan; Kiran Afshan; Neil D. Sargison; Martha Betson; Sabika Firasat; Umer Chaudhry (Acta Parasitologica, 2023)
Purpose Dicrocoeliosis can be an important cause of production loss in ruminants due to the cost of liver condemnation at slaughter. The aim of the present study was to determine the prevalence of Dicrocoelium infection and to predict the ecological niches and climatic variables that support dicrocoeliosis in the Himalayan ranges of Pakistan. Methods and Results Dicrocoelium was detected in 33 of 381 liver samples and 238 of 6060 blood samples taken from sheep and goat herds in the area. The prevalence of dicrocoeliosis was higher in sheep than in goats and highest in females aged more than 3 years. An environmental risk map was created to predict active zones of transmission and showed the highest probability values in central parts of the Chitral district in the northwest of Pakistan. Climatic variables of the mean monthly diurnal temperature range (Bio2), annual precipitation (Bio12), and normalised difference vegetation index (NDVI) were found to be significantly ( p Dicrocoelium infection. Conclusion Together, the findings of this study demonstrate the most suitable ecological niches and climatic variables influencing the risk of dicrocoeliosis in the Himalayan ranges of Pakistan. The methods and results could be used as a reference to inform the control of dicrocoeliosis in the region.

Task-specific polymeric membranes to achieve high gas-liquid mass transfer - Muhammad Tayyab Khalid; Tanzila Anjum; Asim Laeeq Khan; Fahad Rehman; Muhammad Aslam; Mazhar Amjad Gilani; Faheem Hassan Akhtar; Mungyu Lee; In Seop Chang; Muhammad Yasin (Chemosphere, 2023)

Photocatalytic degradation of industrial dye using hybrid filler impregnated poly-sulfone membrane and optimizing the catalytic performance using Box-Behnken design - Sadaf Ul Hassan; Sidra Shafique; Bushra Anees Palvasha; Muhammad Haris Saeed; Syed Ali Raza Naqvi; Sohail Nadeem; Syed Irfan; Toheed Akhter; Asim Laeeq Khan; Muhammad Shahid Nazir; Murid Hussain; Young-Kwon Park (Chemosphere, 2023)

Mixed micellar solubilization for procion blue MxR entrapment and optimization of necessary parameters for micellar enhanced ultrafiltration - Amnah Yusaf; Muhammad Usman; Muhammad Ibrahim; Asim Mansha; Atta ul Haq; Hafiza Fatima Rehman; Majid Ali (Chemosphere, 2023)

Removal of bisphenol A from synthetic and treated sewage wastewater using magnetron sputtered CuxO/PVDF thin film photocatalytic hollow fiber membrane - Hazirah Syahirah Zakria; Mohd Hafiz Dzarfan Othman; Roziana Kamaludin; Asim Jilani; Muhammad Firdaus Omar; Muhammad Ayub; Muhammad Abdul Razis Saidin; Tonni Agustiono Kurniawan; Norbaya Hashim; Nasehir Khan E.M. Yahaya; Nirmala Devi A/P Kerisnan@Kerishnan; Alias Mohammed (Journal of Water Process Engineering, 2023)

Transcriptome and anatomical studies reveal alterations in leaf thickness under long-term drought stress in tobacco - Rayyan Khan; Xinghua Ma; Quaid Hussain; Keling Chen; Saqib Farooq; Muhammad Asim; Xiaochun Ren; Shahen Shah; Yi Shi (Journal of Plant Physiology, 2023)

Activated carbon derived from Dodonaea Viscosa into beads of calcium-alginate for the sorption of methylene blue (MB): Kinetics, equilibrium and thermodynamics - Asim Yaqub; Samia Misbah Syed; Huma Ajab; Muhammad Zia Ul Haq (Journal of Environmental Management, 2023)

Genetically engineered microorganisms for environmental remediation - Hamza Rafeeq; Nadia Afsheen; Sadia Rafique; Arooj Arshad; Maham Intisar; Asim Hussain; Muhammad Bilal; Hafiz M.N. Iqbal (Chemosphere, 2023)

The quest for negative electrode materials for Supercapacitors: 2D materials as a promising family - Muhammad Sufyan Javed; Abdul Mateen; Iftikhar Hussain; Salamat Ali; Sumreen Asim; Awais Ahmad; Elsayed tag Eldin; Majed A. Bajaber; Tayyaba Najam; Weihua Han (Chemical Engineering Journal, 2023)

Microenvironment engineering of Fe-single-atomic-site with nitrogen coordination anchored on carbon nanotubes for boosting oxygen electrocatalysis in alkaline and acidic media - Abba Bala Musa; Mohammad Tabish; Anuj Kumar; Manickam Selvaraj; Muhammad Abubaker Khan; Badria M. Al-Shehri; Muhammad Arif; Muhammad Asim Mushtaq; Shumaila Ibraheem; Yassine Slimani; Saira Ajmal; Tuan Anh Nguyen; et al. (Chemical Engineering Journal, 2023)

Rational design and modulation strategies of Mo-based electrocatalysts and photo/electrocatalysts towards nitrogen reduction to ammonia (NH3) - Muhammad Arif; Muhammad Babar; Umair Azhar; Muhammad Sagir; Muhammad Bilal Tahir; Muhammad Asim Mushtaq; Ghulam Yasin; Muhammad Mubashir; Jun Wei Roy Chong; Kuan Shiong Khoo; Pau Loke Show (Chemical Engineering Journal, 2023)

TPGS Decorated Liposomes as Multifunctional Nano-Delivery Systems - Muhammad Asim Farooq; Natalie L. Trevaskis (Pharmaceutical Research, 2023)
Liposomes are sphere-shaped vesicles that can capture therapeutics either in the outer phospholipid bilayer or inner aqueous core. Liposomes, especially when surface-modified with functional materials, have been used to achieve many benefits in drug delivery, including improving drug solubility, oral bioavailability, pharmacokinetics, and delivery to disease target sites such as cancers. Among the functional materials used to modify the surface of liposomes, the FDA-approved non-ionic surfactant D-alpha-tocopheryl polyethylene glycol succinate (TPGS) is increasingly being applied due to its biocompatibility, lack of toxicity, applicability to various administration routes and ability to enhance solubilization, stability, penetration and overall pharmacokinetics. TPGS decorated liposomes are emerging as a promising drug delivery system for various diseases and are expected to enter the market in the coming years. In this review article, we focus on the multifunctional properties of TPGS-coated liposomes and their beneficial therapeutic applications, including for oral drug delivery, vaccine delivery, ocular administration, and the treatment of various cancers. We also suggest future directions to optimise the manufacture and performance of TPGS liposomes and, thus, the delivery and effect of encapsulated diagnostics and therapeutics.

An overview of genome-wide association mapping studies in Poaceae species (model crops: wheat and rice) - Muhammad Abu Bakar Zia; Muhammad Farhan Yousaf; Arslan Asim; Muhammad Naeem (Molecular Biology Reports, 2022)

Seed Coating with Zinc Oxide Nanofiber (ZnONF) and Urea Improved Zinc Uptake; Recovery Efficiency, Growth, and Yield of Bread Wheat (Triticum aestivum L.) - Muhammad Asim; Wiqar Ahmad; Zahid Qamar; Muhammad Awais; Jaya Nepal; Ijaz Ahmad (Journal of Soil Science and Plant Nutrition, 2022)

BoT-Net: a lightweight bag of tricks-based neural network for efficient LncRNA–miRNA interaction prediction - Muhammad Nabeel Asim; Muhammad Ali Ibrahim; Christoph Zehe; Johan Trygg; Andreas Dengel; Sheraz Ahmed (Interdisciplinary Sciences: Computational Life Sciences, 2022)
Background and objective: Interactions of long non-coding ribonucleic acids (lncRNAs) with micro-ribonucleic acids (miRNAs) play an essential role in gene regulation, cellular metabolic, and pathological processes. Existing purely sequence based computational approaches lack robustness and efficiency mainly due to the high length variability of lncRNA sequences. Hence, the prime focus of the current study is to find optimal length trade-offs between highly flexible length lncRNA sequences. Method The paper at hand performs in-depth exploration of diverse copy padding, sequence truncation approaches, and presents a novel idea of utilizing only subregions of lncRNA sequences to generate fixed-length lncRNA sequences. Furthermore, it presents a novel bag of tricks-based deep learning approach “Bot-Net” which leverages a single layer long-short-term memory network regularized through DropConnect to capture higher order residue dependencies, pooling to retain most salient features, normalization to prevent exploding and vanishing gradient issues, learning rate decay, and dropout to regularize precise neural network for lncRNA–miRNA interaction prediction. Results BoT-Net outperforms the state-of-the-art lncRNA–miRNA interaction prediction approach by 2%, 8%, and 4% in terms of accuracy, specificity, and matthews correlation coefficient. Furthermore, a case study analysis indicates that BoT-Net also outperforms state-of-the-art lncRNA–protein interaction predictor on a benchmark dataset by accuracy of 10%, sensitivity of 19%, specificity of 6%, precision of 14%, and matthews correlation coefficient of 26%. Conclusion In the benchmark lncRNA–miRNA interaction prediction dataset, the length of the lncRNA sequence varies from 213 residues to 22,743 residues and in the benchmark lncRNA–protein interaction prediction dataset, lncRNA sequences vary from 15 residues to 1504 residues. For such highly flexible length sequences, fixed length generation using copy padding introduces a significant level of bias which makes a large number of lncRNA sequences very much identical to each other and eventually derail classifier generalizeability. Empirical evaluation reveals that within 50 residues of only the starting region of long lncRNA sequences, a highly informative distribution for lncRNA–miRNA interaction prediction is contained, a crucial finding exploited by the proposed BoT-Net approach to optimize the lncRNA fixed length generation process. Availability: BoT-Net web server can be accessed at https://sds_genetic_analysis.opendfki.de/lncmiRNA/. Graphic Abstract

Consumption of Citrus mealybug, Planococcus citri by two predators, Cryptolaemus montrouzieri Mulsant and Chrysoperla carnea (Stephen), under controlled conditions - Rehana Bibi; Munir Ahmad; Asim Gulzar; Muhammad Tariq; Muneer Ahmad (International Journal of Tropical Insect Science, 2022)

Simultaneous adsorptive removal of three fluoroquinolones using humic acid modified hydrogel beads - Muhammad Zaheer Afzal; Salma Hameed; Muhammad Mohiuddin; Asim Abbasi (Environmental Science and Pollution Research, 2022)

Host plant resistance for fall armyworm management in maize: relevance, status and prospects in Africa and Asia - Boddupalli M. Prasanna; Anani Bruce; Yoseph Beyene; Dan Makumbi; Manje Gowda; Muhammad Asim; Samuel Martinelli; Graham P. Head; Srinivas Parimi (Theoretical and Applied Genetics, 2022)
Key message Sustainable control of fall armyworm (FAW) requires implementation of effective integrated pest management (IPM) strategies, with host plant resistance as a key component. Significant opportunities exist for developing and deploying elite maize cultivars with native genetic resistance and/or transgenic resistance for FAW control in both Africa and Asia. Abstract The fall armyworm [ Spodoptera frugiperda (J.E. Smith); FAW] has emerged as a serious pest since 2016 in Africa, and since 2018 in Asia, affecting the food security and livelihoods of millions of smallholder farmers, especially those growing maize. Sustainable control of FAW requires implementation of integrated pest management strategies, in which host plant resistance is one of the key components. Significant strides have been made in breeding elite maize lines and hybrids with native genetic resistance to FAW in Africa, based on the strong foundation of insect-resistant tropical germplasm developed at the International Maize and Wheat Improvement Center, Mexico. These efforts are further intensified to develop and deploy elite maize cultivars with native FAW tolerance/resistance and farmer-preferred traits suitable for diverse agro-ecologies in Africa and Asia. Independently, genetically modified Bt maize with resistance to FAW is already commercialized in South Africa, and in a few countries in Asia (Philippines and Vietnam), while efforts are being made to commercialize Bt maize events in additional countries in both Africa and Asia. In countries where Bt maize is commercialized, it is important to implement a robust insect resistance management strategy. Combinations of native genetic resistance and Bt maize also need to be explored as a path to more effective and sustainable host plant resistance options. We also highlight the critical gaps and priorities for host plant resistance research and development in maize, particularly in the context of sustainable FAW management in Africa and Asia.

Determinants of risk attitude and risk perception under changing climate among farmers in Punjab, Pakistan - Muhammad Farhan; Muhammad Asim Yasin; Khuda Bakhsh; Rafaqet Ali; Sami Ullah; Saad Munir (Natural Hazards, 2022)

Neurotoxic effects of environmental contaminants—measurements, mechanistic insight, and environmental relevance - Nadia Afsheen; Sadia Rafique; Hamza Rafeeq; Kanwal Irshad; Asim Hussain; Zille Huma; Vineet Kumar; Muhammad Bilal; Lotfi Aleya; Hafiz M. N. Iqbal (Environmental Science and Pollution Research, 2022)

SARS-COV-2/COVID-19: scenario, epidemiology, adaptive mutations, and environmental factors - Asma Asghar; Hafiz Muhammad Imran; Naheed Bano; Sadia Maalik; Sajida Mushtaq; Asim Hussain; Sunita Varjani; Lotfi Aleya; Hafiz M. N. Iqbal; Muhammad Bilal (Environmental Science and Pollution Research, 2022)

Catalytic potential of endophytes facilitates synthesis of biometallic zinc oxide nanoparticles for agricultural application - Saddam Saqib; Amna Nazeer; Muhammad Ali; Wajid Zaman; Muhammad Younas; Asim Shahzad; Sunera; Momina Nisar (BioMetals, 2022)

Do Agriculture Technologies Influence Carbon Emissions in Pakistan? Evidence based on ARDL technique - Rafaqet Ali; Rabia Ishaq; Khuda Bakhsh; Muhammad Asim Yasin (Environmental Science and Pollution Research, 2022)

Evaluation of insecticidal activity of Beauveria bassiana against different instar larvae of Plutella xylostella by using two different methods of application - Muhammad Shehzad; Muhammad Tariq; Qurban Ali; Asad Aslam; Tariq Mukhtar; Muhammad Faheem Akhtar; Asim Gulzar; Muhammad Faisal (International Journal of Tropical Insect Science, 2022)

Biological Evaluation of Synthesized Schiff Base-Metal Complexes Derived from Sulfisomidine - Amina Mumtaz; Tariq Mahmud; Maryam Khalid; Huma Khan; Aatika Sadia; Malka M. Samra; Muhammad Asim Raza Basra (Journal of Pharmaceutical Innovation, 2022)

Comparative microbiome analysis of Diaphorina citri and its associated parasitoids Tamarixia radiata and Diaphorencyrtus aligarhensis reveals Wolbachia as a dominant endosymbiont - Hafiza Javaria Ashraf; Luis Carlos Ramos Aguila; Komivi Senyo Akutse; Muhammad Ilyas; Asim Abbasi; Xiaofang Li; Liande Wang (Environmental Microbiology, 2022)
Summary Microbiome analysis in a host–parasitoid interaction network was conducted to compare the taxonomic composition of bacterial communities of Diaphornia citri , Tamarixia radiata , and Diaphorencyrtus aligarhensis . The comparative analysis revealed differences in the composition and diversity of the symbiont populations across the host and its associated parasitoids. Proteobacteria was the most dominant phylum, representing 67.80% of the total bacterial community, while Candidatus Profftella armature and Wolbachia were the dominant genera across the host and parasitoids. There were clear differences observed in alpha and beta diversity of microbiota through the host and its associated parasitoids. The function prediction of bacterial communities and Pearson correlation analysis showed that specific bacterial communities displayed positive correlations with the carbohydrate metabolism pathway. Furthermore, when symbiotic bacteria were eliminated using a broad‐spectrum antibiotic, tetracycline hydrochloride, the parasitoids' median survival time and longevity were significantly reduced. We confirmed the physiological effects of symbiotic bacteria on the fitness of parasitoids and demonstrated the effect of antibiotics in decreasing the food intake and measurement of amino acids in the hemolymph. This study sheds light on basic information about the mutualism between parasitoids and bacteria, which may be a potential source for biocontrol strategies for citrus psyllid, especially D. citri .

Dendritic Cell–Targeted Therapies to Treat Neurological Disorders - Asim Hussain; Hamza Rafeeq; Nimra Munir; Zara Jabeen; Nadia Afsheen; Khalil ur Rehman; Muhammad Bilal; Hafiz M. N. Iqbal (Molecular Neurobiology, 2022)

Modeling of rainfall–runoff events using HEC-HMS model in southern catchments of Jerusalem Desert-Palestine - Mohammad Omar Ahmad Shakarneh; Asim Jahangir Khan; Qaisar Mahmood; Romana Khan; Muhammad Shahzad; Adnan Ahmad Tahir (Arabian Journal of Geosciences, 2022)

Tetraconodon and Sivachoerus (Suidae) from Dhok Pathan and Hasnot area of Potwar Plateau, northern Pakistan - Muhammad Adeeb Babar; Kiran Aftab; Muhammad Akbar Khan; Sayyad Ghyour Abbas; Muhammad Asim; Muhammad Akhtar (Arabian Journal of Geosciences, 2021)

Impregnation on activated carbon for removal of chemical warfare agents (CWAs) and radioactive content - Sidra Shaoor Kiani; Amjad Farooq; Masroor Ahmad; Naseem Irfan; Mohsan Nawaz; Muhammad Asim Irshad (Environmental Science and Pollution Research, 2021)

Venlafaxine demonstrated anti-arthritic activity possibly through down regulation of TNF-α, IL-6, IL-1β, and COX-2 - Mater Hussen Mahnashi; Zeeshan Jabbar; Alamgeer; Hafiz Muhammad Irfan; Mulazim Hussain Asim; Muhammad Akram; Ahmed Saif; Mohammed Abdulrahman Alshahrani; Mohammed Ali Alshehri; Saeed Ahmed Asiri (Inflammopharmacology, 2021)

Population structure and phylogenetic relationship of Peach [Prunus persica (L.) Batsch] and Nectarine [Prunus persica var. nucipersica (L.) C.K. Schneid.] based on retrotransposon markers - Hina Naeem; Faisal Saeed Awan; Peter Michael Dracatos; Muhammad Wasim Sajid; Shahzad Saleem; Qudsia Yousafi; Muhammad Saad Khan; Asim Mehmood; Bushra Zulfiqar (Genetic Resources and Crop Evolution, 2021)

New remains of Gazella (Bovidae) from Middle Miocene, Pakistan - Muhammad Akbar Khan; Muhammad Asim; Muhammad Adeeb Babar; Sayyed Ghyour Abbas; Muhammad Khalil Nawaz; Qudeer Ahmad (Arabian Journal of Geosciences, 2021)

Geological and petrographic investigations of the Miocene Molasse deposits in Sub-Himalayas, District Sudhnati, Pakistan - Asim Javed; Ali Wahid; Muhammad Saleem Mughal; Muhammad Sabir Khan; Raja Saad Qammar; Syed Haroon Ali; Numair Ahmad Siddiqui; Muhammad Atif Iqbal (Arabian Journal of Geosciences, 2021)

Synergistic Effect of Urease and Nitrification Inhibitors in the Reduction of Ammonia Volatilization - Asim Hussain; Nazish Jahan; Zara Jabeen; Khalil Ur Rehman; Hamza Rafeeq; Muhammad Bilal; Hafiz M. N. Iqbal (Water, Air, & Soil Pollution, 2021)

Use of multivariate adaptive regression splines for prediction of body weight from body measurements in Marecha (Camelus dromedaries) camels in Pakistan - Cem Tırınk; Ecevit Eyduran; Asim Faraz; Abdul Waheed; Nasir Ali Tauqir; Muhammad Shahid Nabeel; Mohammad Masood Tariq; Irfan Shahzad Sheikh (Tropical Animal Health and Production, 2021)

Impact of economic capabilities and population agglomeration on PM2.5 emission: empirical evidence from sub-Saharan African countries - Summaira Malik; Asim Iqbal; Asma Imran; Muhammad Usman; Muhammad Nadeem; Saira Asif; Awais Bokhari (Environmental Science and Pollution Research, 2021)

CO2 separation by supported liquid membranes synthesized with natural deep eutectic solvents - Usman Saeed; Asim Laeeq Khan; Mazhar Amjad Gilani; Muhammad Aslam; Asad Ullah Khan (Environmental Science and Pollution Research, 2021)

Chemical composition of gemstones and characterization of their host pegmatites and country rocks from Chumar Bakhoor, Gilgit-Baltistan, Pakistan: implications for the source of gem-forming fluids - Amjad Hussain; Muhammad Tahir Shah; Mohammad Arif; Muhammad Hassan Agheem; Muhammad Saleem Mughal; Shakir Ullah; Syed Asim Hussain; Izhar Sadiq (Arabian Journal of Geosciences, 2021)

Effect of profenofos and citrus oil on Cryptolaemus montrouzieri Mulsant and Chrysoperla carnea Stephens, key predators of citrus mealybug, Planococcus citri (Risso), under laboratory conditions - Rehana Bibi; Munir Ahmad; Asim Gulzar; Muhammad Tariq (International Journal of Tropical Insect Science, 2021)

RETRACTED ARTICLE: Anti-rheumatic activity of pseudoephedrine (a substituted phenethylamine) in complete Freund’s adjuvant-induced arthritic rats by down regulating IL-1β, IL-6 and TNF-α as well as upregulating IL-4 and IL-10 - Haseeb Ahsan; Hafiz Muhammad Irfan; Alamgeer; Muhammad Shahzad; Mulazim Hussain Asim; Muhammad Akram; Muhammad Shoaib Zafar (Inflammopharmacology, 2021)

Prediction of live body weight based on body measurements in Thalli sheep under tropical conditions of Pakistan using CART and MARS - Asim Faraz; Cem Tirink; Ecevit Eyduran; Abdul Waheed; Nasir Ali Tauqir; Muhammad Shahid Nabeel; Mohammad Masood Tariq (Tropical Animal Health and Production, 2021)

Micro-morphological response of some native dicotyledonous species to particulate pollutants emitted from stone crushing activities - Iftikhar Ahmad; Lubaba Shamsi; Mansoor Hameed; Sana Fatima; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Muhammad Ashraf; Anum Javaid; Muhammad Asim Sultan (Environmental Science and Pollution Research, 2021)

Correction to: In Silico Evaluation of Food Derived Bioactive Peptides as Inhibitors of Angiotensin Converting Enzyme (ACE) - Qudsia Yousafi; Jannat Batool; Muhammad Saad Khan; Tamsila Perveen; Muhammad Wasim Sajid; Abrar Hussain; Asim Mehmood; Shahzad Saleem (International Journal of Peptide Research and Therapeutics, 2021)

In Silico Evaluation of Food Derived Bioactive Peptides as Inhibitors of Angiotensin Converting Enzyme (ACE) - Qudsia Yousafi; Jannat Batool; Muhammad Saad Khan; Tamsila Perveen; Muhammad Wasim Sajid; Abrar Hussain; Asim Mehmood; Shahzad Saleem (International Journal of Peptide Research and Therapeutics, 2021)

CO2 from waste to resource by developing novel mixed matrix membranes - Adeel Shakoor; Asim Laeeq Khan; Parveen Akhter; Muhammad Aslam; Muhammad Roil Bilad; Ibrahim M. Maafa; Konstantinos Moustakas; Abdul-Sattar Nizami; Murid Hussain (Environmental Science and Pollution Research, 2021)

Relationship between adaptation to climate change and provincial government expenditure in Pakistan - Khuda Bakhsh; Aasma Latif; Rafaqet Ali; Muhammad Asim Yasin (Environmental Science and Pollution Research, 2021)

A novel landslide susceptibility mapping portrayed by OA-HD and K-medoids clustering algorithms - Jian Hu; Kaibin Xu; Genglong Wang; Youcun Liu; Muhammad Asim Khan; Yimin Mao; Maosheng Zhang (Bulletin of Engineering Geology and the Environment, 2021)

Characterization of fungal flora associated with sternorrhyncha insects of cotton plants - Waheed Anwar; Kiran Nawaz; Muhammad Asim Javed; Adnan Akhter; Ahmad Ali Shahid; Muhammad Saleem Haider; Muhammad Zia Ur Rehman; Sajid Ali (Biologia, 2021)

Impact of better cotton initiative on health cost and pesticide exposure of women cotton pickers in Punjab, Pakistan - Muhammad Asim Yasin; Khuda Bakhsh; Rafaqet Ali; Hafiz Irshad Hussain (Environmental Science and Pollution Research, 2021)

Effect of silicon on tritrophic interaction of cotton, Gossypium hirsutum (Linnaeus), Bemisia tabaci (Gennadius) (Homoptera: Aleyrodidae) and the predator, Chrysoperla carnea (Stephens) (Neuroptera: Chrysopidae) - Asim Abbasi; Muhammad Sufyan; Muhammad Jalal Arif; Shahbaz Talib Sahi (Arthropod-Plant Interactions, 2020)

Pregnancy status and thyroid function in semi-intensive-kept Marecha she-camels (Camelus dromedarius): managerial implications - Asim Faraz; Carlos Iglesias Pastrana; Annamaria Passantino; Ayman Balla Mustafa; Abdul Waheed; Nasir Ali Tauqir; Muhammad Shahid Nabeel (Tropical Animal Health and Production, 2020)

Synthesis of nickel nanoparticles using Citrullus colocynthis stem extract for remediation of Reactive Yellow 160 dye - Shumaila Kiran; Muhammad Asim Rafique; Sarosh Iqbal; Sofia Nosheen; Saba Naz; Abdur Rasheed (Environmental Science and Pollution Research, 2020)

Theranostic applications of smart nanomedicines for tumor-targeted chemotherapy: a review - Ajkia Zaman Juthi; Md Aquib; Muhammad Asim Farooq; Sana Ghayas; Farah Khalid; George Frimpong Boafo; Dickson Pius Wande; Daulat Haleem Khan; Tasnim Zaman Bithi; Rohit Bavi; Bo Wang (Environmental Chemistry Letters, 2020)

Hydrocarbon degradation in oily sludge by bacterial consortium assisted with alfalfa (Medicago sativa L.) and maize (Zea mays L.) - Asim Shahzad; Samina Siddiqui; Asghari Bano; Shehla Sattar; Muhammad Zaffar Hashmi; Mingzhou Qin; Abdul Shakoor (Arabian Journal of Geosciences, 2020)

Climate change–induced human conflicts and economic costs in Pakistani Punjab - Khuda Bakhsh; Karim Abbas; Sarfraz Hassan; Muhammad Asim Yasin; Rafaqet Ali; Najid Ahmad; Muhammad Waqas Alam Chattha (Environmental Science and Pollution Research, 2020)

MUCO-DIS: a New AFM-Based Nanoscale Dissolution Technique - Muhammad Usman Ghori; Jorabar Singh Nirwan; Taimoor Asim; Younes Chahid; Samia Farhaj; Zara Khizer; Peter Timmins; Barbara R. Conway (AAPS PharmSciTech, 2020)
Mucoadhesion-based drug delivery systems have recently gained interest because of their bio-adhesion capability, which results in enhanced residence time leading to prolonged duration of action with the mucosal surface, potentially improving compliance and convenience. Mucoadhesion testing of these formulations is widely reported; however, this is technically challenging due to the absence of any standard methods and difficulty in conducting mucoadhesion, formulation-mucosal surface interaction, mucosal surface topography and drug release in a single experiment. As these measurements are currently conducted separately, on replicate formulations, results can often be subjective and difficult to correlate. Hence, the aim of the present study was to develop a new AFM-based single-entity ex vivo muco-dissolution (MUCO-DIS) technique to simultaneously evaluate mucoadhesion force, 3D surface topography, polymer dissolution and drug release characteristics. To demonstrate the potential of the current technique, the interactions between model pectin microparticles containing metformin HCl and a range of gastrointestinal mucosal surfaces (gastric, small intestine, large intestine and buccal) were studied. This novel system has not only successfully determined the mucoadhesion force, polymer dissolution and drug release information but has also highlighted the difference in microparticle performance with different mucosal targets. The current work has highlighted the potential of this newly developed MUCO-DIS system and we believe this will be a valuable tool for characterising these popular pharmaceutical formulations. This technique could also provide an opportunity to other scientific fields to evaluate materials, substrate behaviour and their interactions in their hydrated state at nanoscale with real-time chemical and surface mapping.

Synthesis of Ligand Functionalized ErbB-3 Targeted Novel DNA Nano-Threads Loaded with the Low Dose of Doxorubicin for Efficient In Vitro Evaluation of the Resistant Anti-Cancer Activity - Mirza Muhammad Faran Ashraf Baig; Wing-Fu Lai; Anam Ahsan; Mehreen Jabeen; Muhammad Asim Farooq; Reyaj Mikrani; Muhammad Abbas; Muhammad Naveed; Said Abasse Kassim; Faisal Raza; Afzal Ahmed Dar; Muhammad Tayyab Ansari (Pharmaceutical Research, 2020)

Food Protein-Based Nanodelivery Systems for Hydrophobic and Poorly Soluble Compounds - Mily Bazezy Joelle Maviah; Muhammad Asim Farooq; Rukhshona Mavlyanova; Hanitrarimalala Veroniaina; Mensura Sied Filli; Md Aquib; Samuel Kesse; Kofi Oti Boakye-Yiadom; Bo Wang (AAPS PharmSciTech, 2020)

Ketamine Alleviates Fear Generalization Through GluN2B-BDNF Signaling in Mice - Muhammad Asim; Bo Hao; Yu-Han Yang; Bu-Fang Fan; Li Xue; Yan-Wei Shi; Xiao-Guang Wang; Hu Zhao (Neuroscience Bulletin, 2020)

Middle Miocene Giraffokeryx (Giraffidae) with marks of enamel hypoplasia from Dhok Bun Amir Khatoon, Punjab, Pakistan - Muhammad Akbar Khan; Muhammad Asim (Arabian Journal of Geosciences, 2020)

Mixed matrix membranes incorporated with sonication-assisted ZIF-8 nanofillers for hazardous wastewater treatment - Mohsin Ali; Muhammad Aslam; Amin Khan; Mazhar Amjad Gilani; Asim Laeeq Khan (Environmental Science and Pollution Research, 2019)

Nanocarrier-mediated co-delivery systems for lung cancer therapy: recent developments and prospects - Muhammad Asim Farooq; Md Aquib; Daulat Haleem Khan; Sana Ghayas; Anam Ahsan; Muhammad Ijaz; Parikshit Banerjee; Maqsood Ahmed Khan; Muhammad Masood Ahmad; Bo Wang (Environmental Chemistry Letters, 2019)

Recent advances in the delivery of disulfiram: a critical analysis of promising approaches to improve its pharmacokinetic profile and anticancer efficacy - Muhammad Asim Farooq; Md Aquib; Daulat Haleem Khan; Zahid Hussain; Anam Ahsan; Mirza Muhammad Faran Ashraf Baig; Dickson Pius Wande; Muhammad Masood Ahmad; Hafiz Muhammad Ahsan; Jiang Jiajie; Bo Wang (DARU Journal of Pharmaceutical Sciences, 2019)

Per capita income, trade openness, urbanization, energy consumption, and CO2 emissions: an empirical study on the SAARC Region - Muhammad Asim Afridi; Sampath Kehelwalatenna; Imran Naseem; Muhammad Tahir (Environmental Science and Pollution Research, 2019)

Development and Evaluation of Optimized Thiolated Chitosan Proniosomal Gel Containing Duloxetine for Intranasal Delivery - Maryam khatoon; Muhammad Farhan Sohail; Gul Shahnaz; Fiza ur Rehman; Fakhar-ud-Din; Asim ur Rehman; Naseem Ullah; Umair Amin; Gul Majid Khan; Kifayat Ullah Shah (AAPS PharmSciTech, 2019)

Correction to: Sedimentological impact on reservoir quality of Es1 sandstone of Shahejie formation, Nanpu Sag, East China - Muhammad Kashif; Yingchang Cao; Guanghui Yuan; Muhammad Asif; Wang Jian; Wang Zhukhun; Saif Ur Rehman; Atif Zafar; Muhammad Kamran; Orkhan Isgandarov; Asim Falak Naz (Arabian Journal of Geosciences, 2019)

Sedimentological impact on reservoir quality of Es1 sandstone of Shahejie formation, Nanpu Sag, East China - Muhammad Kashif; Yingchang Cao; Guanghui Yuan; Muhammad Asif; Wang Jian; Wang Zhukhun; Saif Ur Rehman; Atif Zafar; Muhammad Kamran; Orkhan Isgandarov; Asim Falak Naz (Arabian Journal of Geosciences, 2019)

Comparative efficiency of peanut shell and peanut shell biochar for removal of arsenic from water - Muhammad Sohail Sattar; Muhammad Bilal Shakoor; Shafaqat Ali; Muhammad Rizwan; Nabeel Khan Niazi; Asim Jilani (Environmental Science and Pollution Research, 2019)

Environmental and economic impacts of better cotton: a panel data analysis - Sundas Zulfiquar; Muhammad Asim Yasin; Khuda Bakhsh; Rafaqet Ali; Samiullah; Saad Munir (Environmental Science and Pollution Research, 2019)

An empirical investigation of the determinants of CO2 emissions: evidence from Pakistan - Imran Khan; Neelofar Khan; Asim Yaqub; Muhammad Sabir (Environmental Science and Pollution Research, 2019)

What determines compliance with cleaner production? An appraisal of the tanning industry in Sialkot, Pakistan - Ihtsham Ul Haq Padda; Muhammad Asim (Environmental Science and Pollution Research, 2019)

Facile hydrothermal synthesis of magnetic adsorbent CoFe2O4/MMT to eliminate antibiotics in aqueous phase: tetracycline and ciprofloxacin - Juan Zhang; Muhammad Asim Khan; Mingzhu Xia; Abdelnasir Mahmoud Abdo; Wu Lei; Chuan Liao; Fengyun Wang (Environmental Science and Pollution Research, 2019)

Application of instantaneous spectral analysis and acoustic impedance wedge modeling for imaging the thin beds and fluids of fluvial sand systems of Indus Basin, Pakistan - Muhammad Tayyab Naseer; Shazia Asim (Journal of Earth System Science, 2018)

Classification of rocks radionuclide data using machine learning techniques - Abdul Razzaq Khan; Adil Aslam Mir; Sharjil Saeed; Muhammad Rafique; Khawaja M. Asim; Talat Iqbal; Abdul Jabbar; Saeed Ur Rahman (Acta Geophysica, 2018)

A comprehensive study on the surface chemistry of particulate matter collected from Jeddah, Saudi Arabia - Asim Jilani; Syed Zajif Hussain; Mohd Hafiz Dzarfan Othman; Usama Zulfiqar; Muhammad Bilal Shakoor; Imran Ullah Khan; Javed Iqbal; Attieh A. Al-Ghamdi; Ahmed Alshahrie (Journal of Atmospheric Chemistry, 2018)

Seismic stratigraphy of the Mianwali and Bannu depressions, north-western Indus foreland basin - Asam Farid; Perveiz Khalid; Muhammad Y. Ali; Muhammad Asim Iqbal; Khan Zaib Jadoon (International Journal of Earth Sciences, 2018)

Porosity prediction of lower cretaceous unconventional resource play, south Indus Basin, Pakistan, using the seismic spectral decomposition technique - Muhammad Tayyab Naseer; Shazia Asim (Arabian Journal of Geosciences, 2018)

Hospital-acquired methicillin-resistant Staphylococcus aureus (MRSA) from Pakistan: molecular characterisation by microarray technology - Bushra Jamil; Darius Gawlik; Muhammad Ali Syed; Asim Ali Shah; Shahid Ahmad Abbasi; Elke Müller; Annett Reißig; Ralf Ehricht; Stefan Monecke (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Antiplatelet activity, molecular docking and QSAR study of novel N′-arylmethylidene-3-methyl-1-phenyl-6-p-chlorophenyl-1H-pyrazolo[3,4-b] pyridine-4-carbohydrazides - Ayesha Ramzan; Sara Siddiqui; Ahmad Irfan; Abdullah G. Al-Sehemi; Aftab Ahmad; Francis Verpoort; Adeel H. Chughtai; Misbahul A. Khan; Munawar A. Munawar; Muhammad Asim Raza Basra (Medicinal Chemistry Research, 2018)

An application of variogram modelling for electrical resistivity soundings to characterize depositional system and hydrogeology of Bannu Basin, Pakistan - Asam Farid; Perveiz Khalid; Khan Zaib Jadoon; Muhammad Asim Iqbal; James Small (Geosciences Journal, 2017)

Seismic activity prediction using computational intelligence techniques in northern Pakistan - Khawaja M. Asim; Muhammad Awais; F. Martínez–Álvarez; Talat Iqbal (Acta Geophysica, 2017)

Application of spectral decomposition for the detection of fluvial sand reservoirs, Indus Basin, SW Pakistan - Muhammad N. Tayyab; Shazia Asim (Geosciences Journal, 2017)

Understanding brassinosteroid-regulated mechanisms to improve stress tolerance in plants: a critical review - Fahim Nawaz; Muhammad Naeem; Bilal Zulfiqar; Asim Akram; Muhammad Yasin Ashraf; Muhammad Raheel; Rana Nauman Shabbir; Rai Altaf Hussain; Irfan Anwar; Muhammad Aurangzaib (Environmental Science and Pollution Research, 2017)

Continuous wavelet transforms of spectral decomposition analyses for fluvial reservoir characterization of Miano Gas Field, Indus Platform, Pakistan - Muhammad Tayyab Naseer; Shazia Asim (Arabian Journal of Geosciences, 2017)

Seismic attributes’ application to evaluate the Goru clastics of Indus Basin, Pakistan - Muhammad Naseer Tayyab; Shazia Asim; Muhammad Mass Siddiqui; Muhammad Naeem; Sarfraz Hussain Solange; Farhan Khan Babar (Arabian Journal of Geosciences, 2017)

Satellite-sensed tropospheric NO 2 patterns and anomalies over Indus, Ganges, Brahmaputra, and Meghna river basins - Zia ul-Haq; Salman Tariq; Muhammad Ali; Asim Daud Rana; Khalid Mahmood (International Journal of Remote Sensing, 2017)

Applications of variogram modeling to electrical resistivity data for the occurrence and distribution of saline groundwater in Domail Plain, northwestern Himalayan fold and thrust belt, Pakistan - Asam Farid; Perviez Khalid; Klian Zaib Jadoon; Muhammad Asim Iqbal; Muhammad Shafique (Journal of Mountain Science, 2017)

Tourism in Austria: biodiversity, environmental sustainability, and growth issues - Muhammad Asad Saleem Malik; Syed Asim Shah; Khalid Zaman (Environmental Science and Pollution Research, 2016)

The impact of seasonal variation on organochlorine pesticide residues in buffalo and cow milk of selected dairy farms from Faisalabad region - Muhammad Wasim Sajid; Muhammad Shamoon; Muhammad Atif Randhawa; Muhammad Asim; Abdul Shakoor Chaudhry (Environmental Monitoring and Assessment, 2016)

Sulphur dioxide loadings over megacity Lahore (Pakistan) and adjoining region of Indo-Gangetic Basin - Zia ul-Haq; Salman Tariq; Muhammad Ali; Khalid Mahmood; Asim Daud Rana (International Journal of Remote Sensing, 2016)

Seismic and well log driven structural and petrophysical analysis of the Lower Goru Formation in the Lower Indus Basin, Pakistan - Muhammad Naeem; Muhammad Kamran Jafri; Sayed S. R. Moustafa; Nassir S. AL-Arifi; Shazia Asim; Farhan Khan; Nisar Ahmed (Geosciences Journal, 2016)

Spectral decomposition application for analyzing the structure and the reservoir potential: a case study of Penobscot, Nova Scotia offshore, Canada - Shazia Asim; Salman Ahmad; Peimin Zhu; Muhammad Tayyab Naseer; Mehwish Butt (Arabian Journal of Geosciences, 2016)

A case study of Precambrian to Eocene sediments’ hydrocarbon potential assessment in Central Indus Basin of Pakistan - Shazia Asim; Peimin Zhu; Shahid Nadeem Qureshi; Muhammad Tayyab Naseer (Arabian Journal of Geosciences, 2015)

Efficacy of silicon priming and fertigation to modulate seedling’s vigor and ion homeostasis of wheat (Triticum aestivum L.) under saline environment - Muhammad Azeem; Naeem Iqbal; Shakila Kausar; M. Tariq Javed; M. Sohail Akram; M. Asim Sajid (Environmental Science and Pollution Research, 2015)

Exogenous application of silicon at the boot stage decreases accumulation of cadmium in wheat (Triticum aestivum L.) grains - Iqbal Hussain; Muhammad Arslan Ashraf; Rizwan Rasheed; Anum Asghar; Muhammad Asim Sajid; Muhammad Iqbal (Brazilian Journal of Botany, 2015)

Satellite remote sensing of total ozone column (TOC) over Pakistan and neighbouring regions - Zia Ul-Haq; Salman Tariq; Asim Daud Rana; Muhammad Ali; Khalid Mahmood; Parvez Shahid (International Journal of Remote Sensing, 2015)

Effect of Thermal Treatment on Meat Proteins with Special Reference to Heterocyclic Aromatic Amines (HAAs) - Muhammad Asim Shabbir; Ali Raza; Faqir Muhammad Anjum; Moazzam Rafiq Khan; Hafiz Ansar Rasul Suleria (Critical Reviews in Food Science and Nutrition, 2015)

Molecular cloning and expression analysis of mannose receptor in blunt snout bream (Megalobrama amblycephala) - Xiaoling Liu; Xiaocheng Tang; Li Wang; Jie Li; Hong Wang; Shun Wei; Rui Fang; Wei Ji; Gailing Yuan; Nan Chen; Zemao Gu; Xueqin Liu; et al. (Molecular Biology Reports, 2014)

A study of aerosol properties over Lahore (Pakistan) by using AERONET data - Muhammad Ali; Salman Tariq; Khalid Mahmood; Asim Daud; Adila Batool; Zia-ul-Haq (Asia-Pacific Journal of Atmospheric Sciences, 2014)

Absorption and Fluorescence Emission Attributes of a Fluorescent dye: 2,3,5,6-Tetracyano-p-Hydroquinone - Muhammad Zahid; Günter Grampp; Asim Mansha; Ijaz Ahmad Bhatti; Sadia Asim (Journal of Fluorescence, 2013)

Hydrostratigraphy and hydrogeology of the western part of Maira area, Khyber Pakhtunkhwa, Pakistan: a case study by using electrical resistivity - Asam Farid; Khanzaib Jadoon; Gulraiz Akhter; Muhammad Asim Iqbal (Environmental Monitoring and Assessment, 2013)

Prevalence of TP53 germ line mutations in young Pakistani breast cancer patients - Muhammad U. Rashid; Sidra Gull; Kashif Asghar; Noor Muhammad; Asim Amin; Ute Hamann (Familial Cancer, 2012)

Identification of the deleterious 2080insA BRCA1 mutation in a male renal cell carcinoma patient from a family with multiple cancer diagnoses from Pakistan - Muhammad U. Rashid; Sidra Gull; Saima Faisal; Saba Khaliq; Kashif Asghar; Neelam Siddiqui; Asim Amin; Ute Hamann (Familial Cancer, 2011)

Serum Electrolyte and Mineral Variations During Pregnancy and Lactation in Nili-Ravi Buffalo - M. Saleem Akhtar; Abdul Asim Farooq; Syed Aun Muhammad; Laeeq Akbar Lodhi; C. Sikandar Hayat; M. Mushtaq Aziz (Biological Trace Element Research, 2010)

Comparative efficacy of diminazene diaceturate and diminazene aceturate for the treatment of babesiosis in horses - Hamad Bin Rashid; Mamoona Chaudhry; Haroon Rashid; Khalid Pervez; Muhammad Arif Khan; Asim Khalid Mahmood (Tropical Animal Health and Production, 2008)